2018
DOI: 10.20463/jenb.2018.0032
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the correlation between anxiety, salivary alpha amylase, cortisol levels, and athletes’ performance in archery competitions

Abstract: [Purpose]This study aimed to analyze the correlation between anxiety, salivary alpha amylase (sAA), and salivary cortisol (sC) changes in athletes showing a high or low level performance in an actual archery competition.[Methods]The participants were female university athletes who participated in the individual 50 m archery competition at the 21st Korean National Archery Team Trials, in July 2018. Based on their game record in the competition, 9 athletes were allocated to the high-performance group (HPG) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…Studies also show that the activity of the SAA system results in the increased secretion of alpha-amylase by salivary glands (17)(18)(19)(20). The alpha-amylase assay in the saliva is a noninvasive method of measuring SAA axis activity (21).…”
Section: Discussionmentioning
confidence: 99%
“…Studies also show that the activity of the SAA system results in the increased secretion of alpha-amylase by salivary glands (17)(18)(19)(20). The alpha-amylase assay in the saliva is a noninvasive method of measuring SAA axis activity (21).…”
Section: Discussionmentioning
confidence: 99%
“…Díaz et al ( 2013 ) reported a relationship between cortisol and mood of swimmers, feelings of tension, anxiety and hostility experienced in response to the stress caused by competition were observed. Moreover, the anxiety provoked by cortisol can reduce precision in motor tasks (Lim, 2018 ; Park et al, 2020 ), and if the precision was attenuated too in beach volleyball players, this is potentially problematic, as the hit action, which is large responsible for the victory (Medeiros et al, 2017 ), is highly dependent on this skill. However, we must exert caution interpreting these small differences (1.41 ± 0.93 vs. 1.80 ± 0.51 ng/ml) as meaningful, given the large fluctuations and variation observed in salivary cortisol (Hayes et al, 2014 , 2016 ), so whether these differences are biologically significant remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study corroborate with other investigations, which also pointed to an association between SAA and psychological factors. In a survey conducted with university athletes in Korea, a positive correlation was identified between anxiety and the increase in SAA activity, demonstrating that there may be correlations between psychological anxiety and physiological anxiety factors, which can cause a decrease in athlete’s performance ( 36 ) . In an investigation carried out with workers from different occupational categories in Canada, the relationship between SAA activity and various psychosocial characteristics related to work was highlighted.…”
Section: Discussionmentioning
confidence: 99%